INNOVATION IN PUBLIC SERVICE BY THE DEPARTMENT OF EDUCATION WEST BANDUNG REGENCY - Muhammad Rizqi Prajab; Dede Sri Kartini (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to analyze public service innovation at the West Bandung Regency Education Office through three main aspects: clarity of benefits, positive impact of innovation programs, and the development of new services. The innovations studied include the Integrated Digital Education Program (PETADIK), Kinanti Journal, and educational podcasts. The research methodology used is a qualitative approach with in-depth interviews conducted with various stakeholders, including school principals and officials from the West Bandung Regency Education Office. The results of the study indicate that the implemented innovations provide clear benefits to the learning process, enhance student engagement, and assist teachers in delivering material effectively. Additionally, these innovative programs have been proven to have a positive impact on improving the quality of education in the region. In terms of new service development, the West Bandung Regency Education Office has shown a strong commitment to continuously adapt to the dynamic needs of education. This study is expected to provide recommendations for educational policy and serve as a reference for further research in the field of educational innovation.